SOSIAOLISASI DAMPAK PERNIKAHAN DINI DI MA DARUSSHOLIHIN NW DARMAJI - Lalu yoga vandita, Yoga (BEGAWE: Jurnal Pengabdian Masyarakat, 2024)
Community service has been carried out by conducting socialization of the impact of early marriage at Madrasah Aliyah Darusholihin NW Darmaji. Our hope is how teenagers become aware and do not easily get married which has a negative impact on themselves and their environment, so that they know the consequences of early marriage and they are given knowledge about positive activities to fill their free time besides studying at school. The success of this activity can be seen from the increase in participants' knowledge through pre-tests and post-tests. So it can be concluded that there is a significant difference in the knowledge of participants in the socialization activity before and after being given material in the socialization activity. There is an understanding from students about early marriage. There is an understanding and knowing the impacts of early marriage. There is an understanding of the negative impacts of early marriage.